Rhythm in the Essay “Feminismo perfumado”, by Alfonsina Storni - Savia Vidales, Antonella Romina (2024)
In this paper, we seek to listen to the rhythm of the essay “Feminismo perfumado,” by Alfonsina Storni, giving attention to the construction of signification, that is, to what the poem does, to its effect. We begin with the notions of rhythm and poem as proposed by Meschonnic, as well as with the notions of syntactic accent and prosodic accent developed by Dessons. This theoretical path supports an analysis that is based on the reading of both the utterance and the enunciation, making it possible to listen to the rhythm of the essay.